Characterization of Biobased Polyurethane Foams Employing Lignin Fractionated from Microwave Liquefied Switchgrass - Xingyan Huang; Cornelis F. De Hoop; Jiulong Xie; Chung-Yun Hse; Jinqiu Qi; Tingxing Hu (International Journal of Polymer Science)
Lignin samples fractionated from microwave liquefied switchgrass were applied in the preparation of semirigid polyurethane (PU) foams without purification. The objective of this study was to elucidate the influence of lignin in the PU matrix on the morphological, chemical, mechanical, and thermal properties of the PU foams. The scanning electron microscopy (SEM) images revealed that lignin with 5 and 10% content in the PU foams did not influence the cell shape and size. The foam cell size became larger by increasing the lignin content to 15%. Fourier transform infrared spectroscopy (FTIR) indicated that chemical interactions occurred between the lignin hydroxyl and isocyanate revealing that lignin was well dispersed in the matrix materials. The apparent density of the foam with 10% lignin increased by 14.2% compared to the control, while the foam with 15% lignin had a decreased apparent density. The effect of lignin content on the mechanical properties was similar to that on apparent density. The lignin containing foams were much more thermally stable than the control foam as evidenced by having higher initial decomposition temperature and maximum decomposition rate temperature from the thermogravimetric analysis (TGA) profiles.